2022
DOI: 10.1017/s146342362200010x
|View full text |Cite
|
Sign up to set email alerts
|

Different definitions of multimorbidity and their effect on prevalence rates: a retrospective study in German general practices

Abstract: Background: Multimorbidity is common among general practice patients and increases a general practitioner’s (GP’s) workload. But the extent of multimorbidity may depend on its definition and whether a time delimiter is included in the definition or not. Aims: The aims of the study were (1) to compare practice prevalence rates yielded by different models of multimorbidity, (2) to determine how a time delimiter influences the prevalence rates and (3) to assess the effects of multimorbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Similarly, Payne et al 13 performed a retrospective cohort study also in Scotland, and found that mental health morbidity was more prevalent in areas of deprivation and was independently associated with increased rates of unplanned hospital admission. Hauswaldt et al 27 examined prevalence of multimorbidity 2+ and multimorbidity 3+ from 3+ in German general practices. They found that women were more likely to be multimorbid than men and the gender ratio remained stable across both definitions, however they did not examine mental-physical multimorbidity which in the current study was more strongly associated with being a woman than the other definitions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Similarly, Payne et al 13 performed a retrospective cohort study also in Scotland, and found that mental health morbidity was more prevalent in areas of deprivation and was independently associated with increased rates of unplanned hospital admission. Hauswaldt et al 27 examined prevalence of multimorbidity 2+ and multimorbidity 3+ from 3+ in German general practices. They found that women were more likely to be multimorbid than men and the gender ratio remained stable across both definitions, however they did not examine mental-physical multimorbidity which in the current study was more strongly associated with being a woman than the other definitions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Multimorbidity represents a growing public health concern and poses a major challenge to healthcare systems [9]. Any person with more than two chronic health conditions suffers from multimorbidity [10]. The fast-developing multimorbidity is often a negative prognostic factor for disability, particularly among the elderly, and is associated with unfavorable intellectual, psychological, and social outcomes [11,12].…”
Section: Non-communicable Diseases Multimorbiditymentioning
confidence: 99%
“…Multimorbidity is defined as the presence of two or more, generally chronic, illnesses in one person [ 1 , 2 ]. The prevalence of multimorbidity in General Practice- as well as in hospitalized patients is high and will most likely continue to increase over the next years [ 3 ].…”
Section: Introductionmentioning
confidence: 99%